Highly efficient copper-based halide single crystals with violet emission for visible light communication. Issue 5 (16th December 2022) - Shi, Yingrui; Liang, Dehai; Mo, Qionghua; Lu, Shirong; Sun, Zhe; Xiao, Hongbin; Qian, Qingkai; Zang, Zhigang
Abstract : One-dimensional K2 CuBr3 single crystals are demonstrated for visible light communication with a high data transmission rate of 248 Mbps, which is more than 33-fold the −3 dB bandwidth. Abstract : K2 CuBr3 single crystals (SCs) are synthesized using a cooling-induced crystallization method with violet emission due to self-trapped excitons (STEs) under photoexcitation. The prepared K2 CuBr3 SCs exhibit a high photoluminescence quantum yield (PLQY, 79.2%) and excellent stability against moisture, heat and UV light. When the K2 CuBr3 SCs are used as a light source for visible light communication the data transmission rate reaches a striking 248 Mbps, which is more than 33-fold the −3 dB bandwidth.